2019
DOI: 10.4084/mjhid.2019.035
|View full text |Cite
|
Sign up to set email alerts
|

Langerans Cell Histiocytosis: Single Center Experience of 25 Years

Abstract: Objectives: To review a single center outcome of patients with Langerhans Cell Histiocytosis diagnosed at a referral tertiary hospital from Turkey.Methods: The files between 1989 and 2014 of 80 patients with LCH were retrospectively analyzed. Results: During the 25 year period, 80 patients were diagnosed with LCH. The median age at diagnosis was 53 months (2-180 months) and median follow-up time of patients was 10 years and 9 months (24 months-25 years). Bone was the most frequently affected organ (n:60, 75%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
3
11
0
1
Order By: Relevance
“…In the current study, the age at presentation was less than 5 years and the median age of diagnosis was 3 years, in concordance with the pediatric literature 1,2,11 . While a few studies show male predominance, 2,12 our study and others 13,14 documented more cases of female children.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, the age at presentation was less than 5 years and the median age of diagnosis was 3 years, in concordance with the pediatric literature 1,2,11 . While a few studies show male predominance, 2,12 our study and others 13,14 documented more cases of female children.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown the incidence of LCH in children to be 2 to 9 cases per million per year with a male preponderance. LCH has a peak incidence at 1‐4 years of age, and children under 1 year are affected more severely 1‐3 . Around 2% cases present in the neonatal age group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective review of a database of patients with LCH over 25 years at a tertiary referral centre in Turkey demonstrated that the most affected organs after bone were skin, soft tissue and liver [6]⋅ This is in line with other reports in the literature.…”
Section: Introductionsupporting
confidence: 84%
“…Close follow‐up is mandatory to rule out the recurrence of the disease, which depends on the degree of tissue involvement and method of treatment. The ten‐year survival rate for a single bone involvement has been reported to be 100% …”
Section: Discussionmentioning
confidence: 99%